Acute Kidney Injury in Patients with Novel Coronavirus Infection COVID-19 After Cardiac Surgery - G. A. Berdnikov; S. I. Rey; M. A. Sagirov; V. S. Selyaev; A. I. Kovalev; D. A. Kosolapov (Неотложная медицинская помощь)
RELEVANCE. The novel coronavirus (SARS-CoV2) infection (COVID-19) was first identified in China and quickly spread throughout the world, becoming a public health emergency. Acute kidney injury (AKI) occurs in 8–60% of patients with COVID-19 and is associated with significant mortality, especially in patients requiring renal replacement therapy (RRT). Identification of risk factors for the development of AKI, analysis of the course of this life-threatening condition, study of the use of RRT and extracorporeal hemocorrection (ECHC) in patients with COVID-19 after cardiac surgery is of significant interest.   AIM OF THE STUDY. To identify risk factors for the development of AKI, assess the incidence of complications and treatment outcomes in patients with COVID-19 after cardiac surgery. To study the experience of using RRT and ECHC methods.   MATERIAL AND METHODS. We examined 23 patients with a confirmed diagnosis of COVID-19 who were treated in the Infectious Diseases Department of the N. V. Sklifosovsky Research Institute for Emergency Medicine in 2021. Of these, 19 were men (82.6%), and 4 — women (17.4%). The mean age of the patients was 42 years. All the patients required emergency cardiac surgery. Depending on the development of AKI, which required the use of RRT and ECHC methods, patients were divided into two groups: in 10 patients with the development of AKI and multiple organ dysfunction, the use of RRT and ECHC methods was required (group 1); in 13 patients without AKI, standard therapy was used (group 2). Twenty-two patients underwent surgery using cardiopulmonary bypass (CPB), and 1 — without CPB. Indications for the use of RRT and ECHC methods in the patients were the development of AKI, including against the background of chronic kidney disease, in accordance with the KDIGO-2012 criteria, as well as sepsis, septic shock, acute respiratory distress syndrome, water-electrolyte imbalance, acid-base imbalance, systemic inflammation and “cytokine storm”.   CONCLUSIONS. 1. In patients with COVID-19 who require cardiac surgery, the development of acute kidney injury worsens the prognosis of the disease and is accompanied by a statistically significant increase in the duration of mechanical ventilation, the median was 3.2 days compared to 1.0 day in group 2, and the period of stay in the intensive care unit was 16.5 days and 9 days, respectively. 2. Mortality was 30 % in group 1, and 15 % in group 2, p = 0.475; in patients with acute kidney injury, there was a tendency towards a more frequent development of postoperative complications — thus, acute cerebrovascular accident occurred in 20 % and 7.7 % of cases, anemia — in 80 % and 53.3 %, respectively, while mediastinal hematoma developed in 20 % of patients in group 1 only. 3. Risk factors for the development of acute kidney injury in the postoperative period were elevated urea levels and a history of chronic kidney disease. In patients of group 1, the level of intraoperative blood loss was 41.7 % higher than in group 2, but the differences were not statistically significant.